2017
DOI: 10.1021/acs.biochem.7b00455
|View full text |Cite|
|
Sign up to set email alerts
|

Mutational Replacements at the “Glycine Hinge” of the Escherichia coli Chemoreceptor Tsr Support a Signaling Role for the C-Helix Residue

Abstract: Bacterial chemoreceptors are dimeric membrane proteins that transmit signals from a periplasmic ligandbinding domain to the interior of the cells. The highly conserved cytoplasmic domain consists of a long hairpin that in the dimer forms a four-helix coiled-coil bundle. The central region of the bundle couples changes in helix packing that occur in the membrane proximal region to the signaling tip, controlling the activity of an associated histidine kinase. This subdomain contains certain glycine residues that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…The functional role of the glycine hinge in chemoreceptor signaling has been a topic of much speculation and is somewhat controversial. Mutational analyses have shown that side chain replacements at the glycine hinge residues impair or abrogate chemotaxis ability (22, 47). Moreover, several studies have suggested that the glycine hinge introduce structural flexibility to the helix bundle, perhaps to allow bending (14, 22).…”
Section: Discussionmentioning
confidence: 99%
“…The functional role of the glycine hinge in chemoreceptor signaling has been a topic of much speculation and is somewhat controversial. Mutational analyses have shown that side chain replacements at the glycine hinge residues impair or abrogate chemotaxis ability (22, 47). Moreover, several studies have suggested that the glycine hinge introduce structural flexibility to the helix bundle, perhaps to allow bending (14, 22).…”
Section: Discussionmentioning
confidence: 99%
“…9A). MH bundle conformational changes, in turn, probably elicit-through an intervening flexible region and glycine hinge-opposing stability shifts in the receptor hairpin tip that modulate CheA kinase activity (24,31,55,56).…”
Section: Discussionmentioning
confidence: 99%
“…(B) Primary structure of the Tsr MH bundle cap. The sequence logo depicts the predominant residues at each MH cap position in 2,428 nonredundant members of the 36H class of chemoreceptors (31,56,81). The corresponding Tsr residues are listed between the MH1 and MH2 logos.…”
Section: Significancementioning
confidence: 99%
“…Mutational analyses of the amino acyl residues at the two hinges have shown that chemotaxis ability is reduced by mutational substitutions at these loci. Substitution of cysteine or alanine for the glycines in the glycine hinge greatly reduced chemotaxis, as well as kinase activation or kinase control through ligand occupancy (28), and a recent, more extensive, mutational analysis observed similar effects of other substitutions (34). The two-helix region of the HAMP hinge corresponds to residues T262, D263, and T264 in Tar (31).…”
Section: Indications That Chemoreceptors Have Flexible Hingesmentioning
confidence: 94%
“…An evolutionary genomics study of Ͼ2,000 sequences of chemoreceptor cytoplasmic domains from Ͼ150 bacterial and archaeal species, reflecting bacterial and archaeal taxonomic diversity, identified the region surrounding the glycine hinge as a conserved flexible bundle subdomain and thus a feature likely to have an important role in chemoreceptor function and/or structure (29). Recent analysis of Ͼ22,500 chemoreceptor sequences from 5,820 species confirmed this identification (34). The observations documented in our current study demonstrate that intact functional chemoreceptors indeed bend at the glycine hinge.…”
Section: Indications That Chemoreceptors Have Flexible Hingesmentioning
confidence: 97%